1998
DOI: 10.1021/bi972441+
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Mismatch and the Incorporation of Peptides into Lipid Bilayers:  A Possible Mechanism for Retention in the Golgi

Abstract: Preferential interaction of trans-membrane alpha-helices whose hydrophobic length matches the hydrophobic thickness of the lipid bilayer could be a mechanism of retention in the Golgi apparatus. We have used fluorescence methods to study the interaction of peptides Ac-K2-G-Lm-W-Ln-K2-A-amide (Pm+n) with bilayers of phosphatidylcholines with chain lengths between C14 and C24. The peptide P22 (m = 10, n = 12) incorporates into all bilayers, but P16 (m = 7, n = 9) does not incorporate into bilayers when the fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
137
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 36 publications
12
137
1
Order By: Relevance
“…Huschilt et al (20) found that a KKGL 16 KK peptide inserted as an ␣-helix at a perpendicular angle into dipalmitoyl phosphatidylcholine membranes. Furthermore, Webb et al (29) established that a hydrophobic peptide core of 17 residues fully incorporated into a membrane composed of lipids with C 18 acyl chains. The efficiency of these relatively short peptides to integrate into membranes is ascribed to the flexibility of the hydrophobic part of the bordering lysine side chains.…”
Section: Fig 3 Properties Of Liposome Fusion Induced By Wt Tms-peptmentioning
confidence: 99%
“…Huschilt et al (20) found that a KKGL 16 KK peptide inserted as an ␣-helix at a perpendicular angle into dipalmitoyl phosphatidylcholine membranes. Furthermore, Webb et al (29) established that a hydrophobic peptide core of 17 residues fully incorporated into a membrane composed of lipids with C 18 acyl chains. The efficiency of these relatively short peptides to integrate into membranes is ascribed to the flexibility of the hydrophobic part of the bordering lysine side chains.…”
Section: Fig 3 Properties Of Liposome Fusion Induced By Wt Tms-peptmentioning
confidence: 99%
“…Previous studies have suggested that these interactions can serve several regulatory roles such as controlling the membrane-association of lytic peptides [1], modulating membrane-protein activity [2], promoting peptide aggregation [3][4][5][6][7], driving the formation of lipid microdomains, inducing segregation of proteins within the membrane [8][9][10], determining protein sorting within the secretion pathway [11,12], and allowing for cell membrane recognition or fusion [13][14][15]. Previous studies of model transmembrane peptides comprised of polyleucine or Ala-Leu repeats of varying lengths in model membrane systems have shown they form stable a-helices [11,[16][17][18][19][20][21][22][23][24]. These peptides commonly contain flanking tryptophans or lysines which are thought to act as anchoring residues that stabilize the helix within the bilayer and discourage peptide aggregation [18,19,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…It also appeared that a hydrophobic mismatch of up to 10 A A could be accommodated before radical deviations in transmembrane orientations or bilayered lipid structures occurred [11]. However, peptide orientations within a bilayer are thought to depend on a variety of sequence-specific factors such as overall hydrophobicity of the membrane-spanning region of the peptide, the length of the hydrophobic region, and the nature of the flanking residues.…”
Section: Introductionmentioning
confidence: 99%
“…16 and 17), such as ordering/disordering of the lipid acyl chains, alterations in helix tilt angle, adaptations of the peptide backbone, and because it has been shown that the type and extent of the responses that occur depend on the composition of the TM helix. For example, Trp-flanked peptides, which were designed to mimic the membrane spanning parts of intrinsic membrane proteins, showed very different responses to hydrophobic mismatch than analogous Lysflanked peptides (14,15).The aims of the present study are to establish whether or not increased association is a general property of transmembrane segments under conditions of hydrophobic mismatch, and to understand the molecular details of any oligomers that are formed. We investigated the association between Trp-flanked peptides that were designed to mimic * This work was supported in part by the Canadian Institutes of Health Research.…”
mentioning
confidence: 97%